RELATIONSHIP BETWEEN CURRICULUM COMPONENTS AND STUDENTS’ ACADEMIC PERFORMANCE IN SOCIAL STUDIES AMONG JUNIOR SECONDARY SCHOOLS IN DELTA CENTRAL SENATORIAL DISTRICT - IGBEN, OBORAKPORORO MORRISON (Sokoto Educational Review, 2025)
The study investigated the relationship between curriculum components and students’ academic performance in social studies among Junior Secondary Schools in the Delta Central senatorial District. Two research questions and hypotheses guided the study. A correlational research design was adopted. The population of the study consisted of 30,790 Junior Secondary Schools (J.S.S) II students in the Delta Central Senatorial District. A sample of 500 J.S.S II students was selected using a multi-stage sampling technique. Four Local Government Areas were drawn from the eight Local Government Areas that make up the Delta Central senatorial District using simple random sampling, ensuring equal representation. Subsequently, 25 J.S.S II students were selected from each school, totaling 500 participants. The instrument for the study was a structured questionnaire developed by the researcher and students’ academic performance scores in Social Studies for the 2023/2024 academic session. The questionnaire, titled "Curriculum Content and Instructional Strategies," consisted of two sections: Section A, which collected personal biodata, and Section B, which contained 32 items divided into two clusters. Cluster one focused on curriculum content, while cluster two focused on instructional strategies. Pearson product moment correlation coefficient was used to test the hypotheses. Findings revealed a significant relationship between curriculum content and students’ academic performance in social studies. Based on these findings, it was recommended that the social studies curriculum be reviewed to ensure it is comprehensive, relevant, and engaging for students.